Cancer stem cells and their implication in breast cancer. (22nd May 2014) - Carrasco, E.; Álvarez, Pablo J.; Prados, José; Melguizo, Consolación; Rama, Ana R.; Aránega, Antonia; Rodríguez‐Serrano, Fernando
Abstract Background The cancer stem cell (CSC) hypothesis on the origin of cancer has recently gained considerable support. CSCs are tumour cells with the capacity for self‐renewal and differentiation that direct the origin and progression of the disease and may be responsible for relapse, metastasis and treatment failures. Design This article reviews breast CSCs (BCSCs) phenotyping, clinical implications and clinical trials focused on BCSCs in breast cancer. Relevant studies were found through PubMed and Clinicaltrials.gov databases. Results Cancer stem cells are identified and isolated using membrane and cell activity markers; in the case of BCSCs, these are CD44+/CD24low/− and show aldehyde dehydrogenase activity, alongside their capacity to grow and form mammospheres. The presence of stem cell properties is associated with a worse outcome. Hence, these cells have important clinical implications, and elucidation of the mechanisms underlying their activity will allow the development of novel effective therapies and diagnostic instruments, improving the prognosis of these patients. Conclusions Standard treatments are directed against the tumour mass and do not eliminate CSCs. There is therefore a need for specific anti‐CSC therapies, and numerous authors are investigating new targets to this end, as reported in this review. It is also necessary for clinical trials to be undertaken to allow this new knowledge to be applied in the clinical setting. However, there have been few trials on anti‐BCSCs therapies to date.